A study of the transport, extraction and co-ordination chemistry of a number of thiourea ligands with a series of transition and post-transition metal ions - Habtu, Michael M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.